Teachers’ Competence and Instructional Experiences in the Implementation of Makabansa 3: Pedagogical Perspectives from Public Elementary Schools in Legislative District V, Schools Division of Isabela - Leal, Baby Jean; Amin, Jessie (Studies in Technology and Education, 2026)
The implementation of the MATATAG Curriculum in the Philippines introduced Makabansa as an integrated learning area designed to strengthen learners’ civic consciousness, cultural identity, values formation, and socio-emotional development through contextualized and interdisciplinary instruction. As one of the newly introduced learning components in the elementary curriculum, Makabansa 3 requires teachers to demonstrate pedagogical flexibility, interdisciplinary competence, and learner-centered instructional practices. This qualitative phenomenological study explored the competence and instructional experiences of teachers implementing Makabansa 3 in public elementary schools in Legislative District V, Schools Division of Isabela. Specifically, the study examined teachers’ pedagogical competencies, instructional approaches, classroom experiences, implementation challenges, and coping mechanisms in delivering Makabansa instruction under the MATATAG Curriculum framework. Twelve public elementary school teachers handling Grade 3 Makabansa classes were purposively selected as participants. Data were gathered through semi-structured interviews, classroom observations, and document analysis of lesson plans and instructional materials. Using Braun and Clarke’s thematic analysis framework, findings revealed that teachers employed contextualized and integrative pedagogical approaches, collaborative learning activities, experiential tasks, and values-oriented instruction to promote active learner engagement. Teachers demonstrated adaptability and commitment despite experiencing challenges related to insufficient instructional materials, limited training opportunities, curriculum unfamiliarity, time constraints, and diverse learner needs. The findings further revealed that continuous professional development, peer collaboration, administrative support, and localized instructional resources significantly contributed to teachers’ instructional competence and confidence in implementing Makabansa 3. The study concludes that successful implementation of Makabansa 3 requires sustained institutional support, comprehensive teacher capacity-building initiatives, and strengthened contextualized learning resources to ensure effective interdisciplinary instruction and meaningful learner development. The findings contribute to the growing discourse on curriculum reform, teacher competence, and elementary education pedagogy in the Philippine educational context.